Understanding the impact of engineered nanoparticles in food - Ng, Louis Cher Seng (2016)
Over the past years, the food industry has been adopting the use of engineered nanomaterials (ENMs) as additives in food products, and it is anticipated that the number of food products containing some level of ENMs will inevitably increase in the near future. Recent studies on the toxicity of nanoparticles have raised concerns over the health and safety of people consuming these “nanofood” products. Thus, it is important to understand the way nanoparticles behave in the body, as well as improve safety checks on food products through the development of methods that enables accurate isolation and characterization of nanoparticles in food. This project studies the behavior of food grade TiO2 (E171), food grade SiO2 (E551) and commercial silver (Ag) nanoparticles in simulated gastrointestinal (GI) tract fluids, and also identifies possible extraction methods that can be used to detect the presence of nanoparticles in common food products. The food-grade nanoparticles were subjected to varying pH, ionic and enzyme concentrations and were subsequently sent for analysis. The results obtained from the study on the individual effects of pH, ionic and enzyme concentration was consistent with past literature, whereby the decrease in pH and increase in ionic concentration led to the decrease in magnitude of the zeta potential and corresponding increase in hydrodynamic size. Although the underlying mechanism behind mixing varying pH, ionic and enzyme concentration could not be fully understood, the results obtained have provided a better understanding on the potential synergistic effects the three conditions had on the nanoparticles. These results will then serve as a basis for future work to move on to the complete formulations of the simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) of the GI tract so that conclusive results can be obtained. In addition, a facile protocol to separate nanoparticles from food products was successfully developed. This serves as a basis for future works to quantify and thoroughly characterize nanoparticles in complex food matrices.